2015
DOI: 10.1037/per0000116
|View full text |Cite
|
Sign up to set email alerts
|

Maternal borderline personality disorder symptoms and convergence between observed and reported infant negative emotional expressions.

Abstract: To date, the influence of maternal borderline personality disorder (BPD) on perceptions of infants’ emotional expressions has not been examined. This study investigated the relation of maternal BPD symptoms to discrepancies between mother-reported and observed infant expressions of fear and anger. Emotional expressions in response to fear- and anger-eliciting stimuli were observed among 101 12–23 month old infants of mothers with a range of BPD symptoms. Mothers also reported on their infants’ past-month fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…As shown in Table 1, the percentage of participants reporting at least moderate impairment from each BPD symptom ranged from 11.3% (for intense anger) to 40.6% (for unstable relationships). Severity of BPD pathology within this sample was comparable to other nonclinical community samples (Whalen, Kiel, Tull, Latzman, & Gratz, 2015). 3…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…As shown in Table 1, the percentage of participants reporting at least moderate impairment from each BPD symptom ranged from 11.3% (for intense anger) to 40.6% (for unstable relationships). Severity of BPD pathology within this sample was comparable to other nonclinical community samples (Whalen, Kiel, Tull, Latzman, & Gratz, 2015). 3…”
Section: Resultssupporting
confidence: 68%
“…3Severity of BPD symptoms (as indexed by endorsement of at least moderate impairment on the BEST) within this sample did not differ significantly from the nonclinical community sample in Whalen et al’s (2015) study (χ 2 s < 2.17, p s > .05), with one exception: The rate of moderate impairment for the symptom of intense anger was lower in this sample than in Whalen et al’s sample, χ 2 (1, 106) = 10.78, p = .001.…”
mentioning
confidence: 79%
“…These findings are consistent with past research indicating a heightened sensitivity to anger cues and a bias toward the perception of anger in BPD (Domes et al, 2008;Sharp & Vanwoerden, 2015;Veague & Hooley, 2014), and suggest that it could be the misattribution of or bias toward perceiving anger in infants that relates to nonsupportive responses to infant negative emotions among mothers with high BPD symptoms. Alternatively, recent research specifically with infants suggests that maternal BPD symptoms are associated with greater convergence between laboratory-assessed and mother-reported infant anger (Whalen, Kiel, Tull, Latzman, & Gratz, 2015). Thus, whereas mothers with low BPD symptoms may minimize their reports of infant anger, mothers with high BPD symptoms may experience a heightened sensitivity to or recognition of anger that is actually present.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, neutral infant expressions were more often perceived as sad (Elliot et al, 2014). Another study looked at discrepancies between mother-reported and researcher observed infant expressions (Whalen, Kiel, Tull, Latzman, & Gratz, 2015). Findings showed that as maternal BPD symptom severity increased, there was greater convergence between mother-reported and observed infant anger.…”
Section: Rejection and Laxnessmentioning
confidence: 99%